Microstructural design and characterisation of alumina/hexaluminate composites. - Asmi, Dwi (Curtin University, 2001)
A study was conducted to investigate a novel route to low cost processing of alumina/calcium-hexaluminate (A/CA6) composites. The objectives of this study were to: (a) develop A/CA6 and ß-spodumene modified A/CA6 composites using an in-situ reaction sintering method and functionally-graded A/CA6 using an infiltration technique, and (b) evaluate the effects of CA6 platelets on the ensuing physical and mechanical properties. The study has revealed that the processing procedures played an important role in the microstructural development of A/CA6 composites. The microstructure-property relationships of these materials were found to be strongly influenced by the presence of CA6 phase.The A/CA6 composites were synthesised by in-situ reaction sintering of alumina powder and (0, 5, 15, 30, 50 and 100 wt%) CA6 precursor. The phase relations and development of this system were monitored using quantitative x-ray diffraction (XRD) and neutron diffraction (ND). Rietveld analysis which showed the CA6 content to increase in proportion with the increase of CA6 precursor added. The XRD study revealed that the CA and CA2 phases started to develop at approximately 1000 and 1100°C and transformed to CA6 phase at 1400T. Similarly, the dynamic high temperature ND study showed that the corresponding calcium aluminates phases commenced to develop at 1000°C and 1200°C and then eventually transformed to CA6 at 1400°C.The presence of the plate-like CA6 grains in the system was revealed by the back-scattered SEM imaging and confirmed by the Ca x-ray map. Although the presence of CA6 caused the reduction of hardness, the fracture toughness of A/CA6 composites were improved when compared with alumina. It was found that the presence of CA6 hindered the processes of sintering and densification in alumina matrix.The use of ß -spodumene had been investigated as a liquid-phase-sintering aid for the densification of A/CA6 composites. XRD, ND, differential thermal analysis (DTA), scanning electron microscopy (SEM) and Vickers indentation were used to characterise the effects of ß -spodumene on the phase relations, densification, microstructure and mechanical properties. The results showed that the presence of ß -spodumene had a profound influence on the phase relations, densification and microstructure of A/CA6 composites. Quantitative XRD and ND Rietveld analysis showed that the addition of > 2.5 wt% ß -spodumene caused the reduction of CA6 content due to the formation of ß -quartz solid solution. The reduction of porosity in the presence of ß -spodumene suggests that it may be used as an effective sintering aid for improving the densification of A/CA6 composites. However improvements in hardness and fracture toughness were not achieved probably due to the presence of large spherical pores as well as the formation of recrystallised ß -spodumene and ß -quartz solid solution.A functionally-graded alumina/calcium-hexaluminate (A/CA6) composite was successfully synthesised through infiltration of porous alumina preform with a solution containing calcium-acetate. The infiltration kinetics of liquid into porous alumina preform had also been investigated. It was found that the infiltration rate equation proposed by Washburn is most suitable for describing the effects of preform sintering temperature, viscosity and multiple infiltrations on the infiltration characteristics. The influence of applied pressure is consistent with the model proposed by Darcy, where the applied pressure enhances the infiltration rate behaviour. Key parameters for the optimum processing conditions of preforms for subsequent infiltration have also been identified.The graded composition character of the functionally-graded A/CA6 composites were characterised by XRD and synchrotron diffraction (SRD). Depth-profiling of compositions with XRD and SRD Rietveld refinement showed that the concentration of CA6 decreased with depth, while that of A1203 increased with depth. Both XRD and SRD results showed that CA and CA2 phases formed initially at 1000°C and 1300°C, respectively, but remained stable even at 1400°C, before eventually transformed to CA6 at 1650°C. These results are consistent with those of dynamic high temperature ND data.The graded microstructure was revealed by SEM back-scattered imaging whereby the content of CA6 platelets was most abundant near the surface and decreased with increasing depth towards the bulk. The presence of CA6 phase in the composite fire at 1400°C was also confirmed by the transmission electron microscopy (TEM) observation in conjunction with energy dispersive spectroscopy (EDS). The hardness results of the graded material showed that the graded-region was softer than the non-graded region as a result of the presence of softer CA6 phase in the former. However, the fracture toughness in the graded region was found to be higher than the non-graded region which might be attributed to the display of toughening processes such as crack deflection and grain bridging.